Developing a differentiated learning approach using smartphone applications to reduce learning loss and enhance students’ motivation in English language learning - Siti Ngaisah; Salma Hira; Ekka Zahra Puspita Dewi; Edi Yulianto (Journal of English Language and Pedagogy, 2025)
This study aims to develop an English language learning model based on a differentiated instruction approach utilizing smartphone applications to reduce learning loss and enhance students' learning motivation. The development model adopted follows the ADDIE framework by Borg & Gall, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The analysis stage was carried out through classroom observations, interviews, and questionnaires to identify learning needs, motivation levels, and students' access to technological resources. The design stage involved developing differentiated learning scenarios in terms of content, process, and product, integrated with smartphone applications such as YouTube, Pinterest, Wemoji and Quizzes for the "Hobby" topic. In the development stage, instructional materials and evaluation instruments were prepared and validated by experts. The implementation was conducted in an English class at a junior high school. This research involved 10 participants as preliminary testing and then 50 students (25 girls and 25 boys) as the main field testing. The students were grouped according to their abilities and interests. Formative and summative evaluations indicated a significant improvement in post-test scores compared to pre-test results, signaling a reduction in learning loss. Furthermore, questionnaire and observational data revealed increased student motivation, particularly in terms of active engagement and sustained interest in learning activities. These findings suggest that differentiated instruction integrated with smartphone applications is an effective and innovative strategy for English language learning, especially in the context of post–learning loss recovery.